Sex Differences in Language Across Early Childhood: Family Socioeconomic Status does not Impact Boys and Girls Equally - Barbu, Stéphanie; Nardy, Aurélie; Chevrot, Jean-Pierre; Guellaï, Bahia; Glas, Ludivine; Juhel, Jacques; Lemasson, Alban (Frontiers in Psychology, 2015)
Child sex and family socioeconomic status (SES) have been repeatedly identified as a source of inter-individual variation in language development; yet their interactions have rarely been explored. While sex differences are the focus of a renewed interest concerning emerging language skills, data remain scarce and are not consistent across preschool years. The questions of whether family SES impacts boys and girls equally, as well as of the consistency of these differences throughout early childhood, remain open. We evaluated consistency of sex differences across SES and age by focusing on how children (N = 262), from 2;6 to 6;4 years old, from two contrasting social backgrounds, acquire a frequent phonological alternation in French – the liaison. By using a picture naming task eliciting the production of obligatory liaisons, we found evidence of sex differences over the preschool years in low-SES children, but not between high-SES boys and girls whose performances were very similar. Low-SES boys’ performances were the poorest whereas low-SES girls’ performances were intermediate, that is, lower than those of high-SES children of both sexes but higher than those of low-SES boys. Although all children’s mastery of obligatory liaisons progressed with age, our findings showed a significant impeding effect of low-SES, especially for boys.